2019
DOI: 10.1038/s41598-019-46995-y
|View full text |Cite
|
Sign up to set email alerts
|

Bedside-measurement of serum cholinesterase activity predicts patient morbidity and length of the intensive care unit stay following major traumatic injury

Abstract: Major traumatic injury (MTI), a life-threatening condition requiring prompt medical intervention, is associated with an extensive inflammatory response often resulting in multiple organ dysfunction. Early stratification of trauma severity and the corresponding inflammation may help optimize resources at the intensive care unit (ICU). The cholinergic system counters inflammation by quickly modulating the immune response. Serum cholinesterase (butyrylcholinesterase, BChE) is an enzyme that hydrolyses acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
13
2
Order By: Relevance
“…Zivkovic et al 10 showed that bedsidemeasurement of BChE activity predicts patient morbidity and length of ICU stay following major traumatic injury. 21 Another study with patients undergoing venoarterial extracorporeal membrane oxygenation therapy after Open access cardiac surgery revealed BChE as a strong predictor of all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Zivkovic et al 10 showed that bedsidemeasurement of BChE activity predicts patient morbidity and length of ICU stay following major traumatic injury. 21 Another study with patients undergoing venoarterial extracorporeal membrane oxygenation therapy after Open access cardiac surgery revealed BChE as a strong predictor of all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…LChE: cholinesterase ≤4244 U L −1 ; NChE, cholinesterase >4244 U L −1 ; NRS, Numeric Rating Scale; *statistically significant differences in NRS between LChE and NChE group (upper cluster-Mann-Whitney U test) and in NRS before and after tramadol within the same group (lower cluster-Wilcoxon test). et al have observed that the plasma activity of ChE after traumainduced systemic inflammation decreases before standard proinflammatory biomarkers began to increase, and confirmed its importance in the early diagnosis of systemic inflammation, and in predicting morbidity and mortality (Zivkovic et al, 2016;Zivkovic et al, 2019). Li et al demonstrated that low ChE activity at the time of hospitalization was an independent risk factor for death in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 91%
“…Cholinergic parameters are associated with a variety of inflammatory markers, including fibrinogen, IL-6, and CRP (18). The measurement of the S-ChE activity can be used to quickly assess the nonneuronal cholinergic activity upon an inflammatory response (19). de Oliveira et al (20) showed that there is a cell-specific mechanism for regulating the expression of AChE in inflammation.…”
Section: Discussionmentioning
confidence: 99%